2014
DOI: 10.6028/nist.tn.1848
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Installation Faults on Heat Pump Performance

Abstract: Numerous studies and surveys indicate that typically-installed HVAC equipment operate inefficiently and waste considerable energy due to different installation errors (faults) such as improper refrigerant charge, incorrect airflow, oversized equipment, leaky ducts. This study seeks to develop an understanding of the impact of different faults on heat pump performance installed in a single-family residential house. It combines building effects, equipment effects, and climate effects in a comprehensive evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Researchers have shown that about 60% of heating, ventilation, and air-conditioning (HVAC) systems have installation, commissioning, and performance problems, leading to as much as a 30% increase in annual energy consumption (Lstiburek 2010;Domanski 2014). The efficient design and improved operation of HVAC systems in homes could lead to significant energy reduction.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have shown that about 60% of heating, ventilation, and air-conditioning (HVAC) systems have installation, commissioning, and performance problems, leading to as much as a 30% increase in annual energy consumption (Lstiburek 2010;Domanski 2014). The efficient design and improved operation of HVAC systems in homes could lead to significant energy reduction.…”
Section: Executive Summarymentioning
confidence: 99%
“…
Executive SummaryBuildings consume about 40% of total energy used in the United States, and residential buildings account for more than half of the energy consumed in buildings.Researchers have shown that about 60% of heating, ventilation, and air-conditioning (HVAC) systems have installation, commissioning, and performance problems, leading to as much as a 30% increase in annual energy consumption (Lstiburek 2010;Domanski 2014). The efficient design and improved operation of HVAC systems in homes could lead to significant energy reduction.The development of commercially available sensors and control-related software in the past decade has resulted in a rapidly growing and changing HVAC control industry.
…”
mentioning
confidence: 99%
“…Residential homes also could potentially benefit from commissioning services, which could be brought into the affordable range for households with application of NILM technology. Approximately 60 percent of HVAC systems have installation, commissioning, and performance problems, leading to as much as a 30 percent increase in annual energy consumption (Lstiburek andPettit 2010 andDomanski et al 2014). Accurate end-use load monitoring identifies malfunctioning equipment both for commissioning and retro-commissioning.…”
Section: The Value Of End-use Load Datamentioning
confidence: 99%
“…21 Numerous field and simulation-based studies have shown installed systems operate sub-optimally because of installation faults. 22 A majority of faults identified at start-up can be corrected, while issues related to poorly designed distribution systems are harder to correct.…”
Section: Smart Systems and Equipmentmentioning
confidence: 99%